2014
DOI: 10.1038/onc.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

Slug is temporally regulated by cyclin E in cell cycle and controls genome stability

Abstract: The transcriptional repressor Slug is best known to control epithelial-mesenchymal transition (EMT) and promote cancer invasion/metastasis. In this study, we demonstrate that Slug is temporally regulated during cell cycle progression. At G1/S transition, cyclin E-cyclin-dependent kinase 2 mediates the phosphorylation of Slug at Ser-54 and Ser-104, resulting in its ubiquitylation and degradation. Non-phosphorylatable Slug is markedly stabilized at G1/S transition compared with wild-type Slug and greatly leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Moreover, the Daxx and ATRX complex is required for histone H3.3 heterochromatin deposition and accounts for H3.3 serine-31 phosphorylation; these mechanisms are abolished by disrupting the Daxx–ATRX complex5961. Recent findings have shown that the Slug protein is tightly regulated at the posttranslational level and its transcriptional activity is negatively controlled by several kinases via a phosphodegron mechanism416263. To address this, we evaluated whether Daxx-bound Slug is subsequently targeted for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Daxx and ATRX complex is required for histone H3.3 heterochromatin deposition and accounts for H3.3 serine-31 phosphorylation; these mechanisms are abolished by disrupting the Daxx–ATRX complex5961. Recent findings have shown that the Slug protein is tightly regulated at the posttranslational level and its transcriptional activity is negatively controlled by several kinases via a phosphodegron mechanism416263. To address this, we evaluated whether Daxx-bound Slug is subsequently targeted for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2D cultured cells also maintained a high level of cellular homogeneity, where~96% of 4T1 cells persisted in an epithelial cell state. Carcinomas of different tissue origin, including lung and gastric, have been documented to undergo EMT, as characterized by a loss in epithelial behaviors like cell polarity and cell-cell adhesion [25] and a decreased proliferation in cells up-regulating EMT genes [26].…”
Section: Discussionmentioning
confidence: 99%
“…using Loupe Cell Browser (10× Genomics) and Seurat (26). The Cell Ranger Single-Cell Software Suite was used to perform sample demultiplexing, barcode processing, and single-cell 3 gene counting.…”
Section: The 4t1-bfp Generationmentioning
confidence: 99%
“…SNAI2 alone sometimes is sufficient to induce EMT, and it is essential for Twist-induced EMT (42). SNAI2 has also been implicated in cancer cell stemness, cell cycle regulation, proliferation, apoptosis, chemotherapy resistance as well as invasion and metastasis (43)(44)(45)(46)(47)(48)(49). SNAI2 expression and activity has been associated with poor clinical outcome in multiple cancer types, including breast cancer (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%